The role of husband support in 3-month injection birth control visits at the Cibeber Cimahi Community Health Center in 2018 - Damai Yanti Simanjuntak (Jurnal Kesehatan Budi Luhur : Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2020)
Background:Family planning services are one in the package of essential reproductive health services that need serious attention, because with the quality family planning services, it will improve the welfare, health of infants and children and reproductive health. The husband is a wife's life partner so the husband's role is considered very important in supporting the successful use of contraception. At the Cibeber Health Center the highest use of contraception is 3-month injection contraception, where women who use it must re-visit according to the allotted time every 3 months. Based on data obtained at the public health, there are many old-age pregnancies, pregnancies with close range and even multi-parity and even grande that occur, one of which is due to the re-visit of contraception that is not on time. The purpose of this study was to determine the number of husband support for wives who use contraception, the number of return visits for 3 months injectable contraception acceptors and the relationship of husband support for 3 months injection visit. The research method used in this research is analytic descriptive using chi square test as a bivariate analysis and questionnaire as a research instrument. The results of this study were 51% of husbands who did not support and 49% of husbands who supported the use of 3 months injection contraception. The result of bivariate analysis is that there is a significant relationship between the role of husband support with 3 months injection contraception visit where the results of the chi square analysis show the p value = 0,000. Discussion in this research women who use contraception must have the support of their husbands so that the continuation of 3-month injection contraception can run well and make repeat visits on time.Keywords: Contraception, Support